Targeted array comparative genomic hybridisation (array CGH) identifies genomic imbalances associated with isolated congenital diaphragmatic hernia (CDH) - Kasemsri Srisupundit (2018)
Objective: Congenital diaphragmatic hernia (CDH) is a congenital birth defect affecting around 1/3000 births. We propose that a significant number of isolated CDH cases have an underlying genetic cause, and that a subset of these result from copy number variations (CNVs) identifiable by array CGH. Methodology: We have designed a custom array targeted at genes and genomic loci associated with CDH. A total of 79 isolated CDH patients were screened using this targeted array. Results: In three patients, we detected genomic imbalances associated with the observed diaphragmatic hernia; a deletion of 8p22-p23.3, 14.2 Mb in size, a 340 kb duplication of Xq13.1 including the ephrin-B1 gene (EFNB1), and mosaicism for trisomy 2. Conclusion: Using this approach, we detected genomic imbalances associated with CDH in 3/79 (4%) isolated CDH patients. Our findings further implicate 8p deletions as being associated with CDH. The duplication of EFNB1 further highlights this gene as a potential candidate involved in diaphragm development. Mosaicism for trisomy 2 is a rare event and unlikely to be a common cause of CDH. Further investigations of isolated CDH patients by array CGH will continue to identify novel submicroscopic loci and refine genomic regions associated with CDH. Copyright © 2010 John Wiley & Sons, Ltd.